Discovery of Novel Drug Candidates for Alzheimer’s Disease by Molecular Network Modeling - Zhou, Jiaxin; Li, Qingyong; Wu, Wensi; Zhang, Xiaojun; Zuo, Zhiyi; Lu, Yanan; Zhao, Huiying; Wang, Zhi (Frontiers in Aging Neuroscience, 2022)
To identify the molecular mechanisms and novel therapeutic agents of late-onset Alzheimer’s disease (LOAD), we performed an integrative network analysis using multiple transcriptomic profiles of human brains. With the hypothesis that AD pathology involves the whole cerebrum, we first identified co-expressed modules across multiple cerebral regions of aging human brain. Among them, two modules (M3 and M8) consisting of 1429 protein-coding genes were significantly enriched with AD-correlated genes. Differential expression analysis of microarray, bulk RNA-seq data revealed the dysregulation of M3 and M8 across different cerebral regions in both normal aging and AD. Cell-type enrichment analysis and DE analysis at single cell resolution indicated the extensive neuronal vulnerability in AD pathogenesis. Transcriptomic-based drug screening from Connectivity Map proposed Gly-His-Lys acetate salt (GHK) as a potential drug candidate that could probably restore the dysregulated genes of M3 and M8 network. Pretreatment with GHK showed neuroprotective effect against amyloid-beta-induced injury in differentiated human neuron-like SH-SY5Y cells. Taken together, our findings uncover a dysregulated network disrupted across multiple cerebral regions in AD and propose pretreatment with GHK as a novel neuroprotective strategy against AD.